Military Connection and Audit Report Lag: Indonesian Evidence - Rizki Rachmadia (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This paper aims to examine the relationship between military connections and audit report lag. The study was carried out using statistical testing on 1,357 firms-year observations listed on the Indonesia Stock Exchange, from 2014 to 2017. The findings show that firms with military connections have relatively shorter audit report lag periods, both large and small firms. . In addition, large-scale firms tend to appoint Big 4 KAP auditors, so as to shorten the audit report lag time. Although there are many studies examining the determinants of audit report lag, few have discussed the impact of military connections. This study is expected to contribute to the literature on audit report lag which is considered a qualitative aspect in assessing the audit efficiency of a company.